DOES INVESTMENT REALLY MATTER? A REGIONAL STUDY ON HUMAN DEVELOPMENT INDEX IN BANDUNG REGENCY - Simamora, Daniel (Publikasi Inspirasi Indonesia, 2025)
This study aims to analyze the impact of investment, proxied by Gross Fixed Capital Formation (GFCF), on the Human Development Index (HDI) in Bandung Regency. An increase in HDI is a fundamental measure of regional development success that goes beyond mere economic growth. Using a quantitative approach, this research applies an Ordinary Least Squares (OLS) regression model to annual time-series data from 2010 to 2024. The investment variable is measured through GFCF data at 2010 constant prices, while the HDI uses the official index released by Statistics Indonesia (BPS). The econometric analysis results indicate that investment has a positive and statistically significant effect on the HDI in Bandung Regency. Each 1% increase in investment realization is, on average, correlated with an increase in the HDI. This finding underscores the crucial role of investment as one of the driving forces of community welfare. The main conclusion of this study is the importance of formulating investment policies that are not only oriented towards achieving value targets (quantity) but also focused on the quality and sectors of investment that can provide a direct and sustainable impact on improving the dimensions of health, education, and a decent standard of living for the people of Bandung Regency.